Motor skills and internalizing problems throughout development: An integrative research review and update of the environmental stress hypothesis research. (January 2019) - Mancini, Vincent; Rigoli, Daniela; Roberts, Lynne; Piek, Jan
Highlights: Numerous studies have evaluated sections of the Environmental Stress Hypothesis. Psychosocial factors mediate/moderate the link between motor skills and internalizing problems. This link has been identified in community samples spanning childhood to adulthood. The strength of pathways in the framework varies. Targets for combined psychosocial and motor skills interventions are identified. Abstract: Background: The Environmental Stress Hypothesis provides a conceptual framework detailing the complex relationship between poor motor skills and internalizing problems. Aims: This integrative research aimed to synthesize studies that have evaluated complex pathways posited in the framework. Method: This study followed the four stages of an integrative research review: (i) problem formation and research aims, (ii) literature search and data collection, (iii) data evaluation and analysis, and (iv) results and discussion. Outcomes and Results: Twelve peer-reviewed, English language studies published within 2010–2018 were identified. These used mostly cross-sectional, correlational methods and provided varying levels of support for relationships posited in the framework in samples spanning early childhood to adulthood. Compared to intrapersonal factors (e.g., self-esteem/ perceived competence), interpersonal factors (e.g., social support, peer problems) were found to more strongly and consistently mediate the relationship between motor skills and internalizing problems. Conclusions and Implications: There is growing empirical support for many of the Environmental Stress Hypothesis pathways. However, research to date is limited in the ability to establish causal relationships between variables, which is integral to the Environmental Stress Hypothesis. Intervention studies provide a useful type of experimental research that could establish causality between variables, while working to improve the physical and psychosocial functioning of people with poor motor skills.